Balanced four‐pole frequency‐agile bandpass filter with constant absolute bandwidth and four transmission zeros. Issue 1 (25th August 2020) - Li, Zhiyou; Tang, Xiaohong; Liu, Yong; Lu, Di; Cai, Zongqi
Abstract: In this letter, a four‐pole balanced frequency‐agile bandpass filter (BAL‐FA‐BPF) with constant absolute bandwidth (CABW) and four transmission zeros (TZs) is reported. This design is based on the advanced coupling matrix technique which ensures the realization of CABW for the filter. The fully‐canonical coupling topology with cross‐coupling and source‐load coupling is adopted, which introduces four TZs for the differential‐mode passband. The tunable half‐wavelength resonators are used and loaded by resistors, which effectively enhances the common‐mode (CM) suppression. The demonstrative BAL‐FA‐BPF has a frequency tuning range of 1.92‐2.97 GHz (42.9%) and keeps the absolute bandwidth within 167 ± 3.7 MHz (2.2%) over entire the FTR. CM suppression is better than 40 dB.